Latino/a children's and young adult writers on the art of storytelling - Aldama, Frederick Luis, 1969- (University of Pittsburgh Press, 2018)
"This book is an original collection of more than thirty interviews led by Frederick Luis Aldama with Latino/a authors working in the genre." --Back cover
Keywords: Hispanic American authors -- Interviews.; Children's literature, American.; Young adult literature, American.; American literature -- Hispanic American authors.; Littérature américaine -- Auteurs américains d'origine latino-américaine.; Littérature pour jeunes adultes américaine.; Littérature de jeunesse américaine.; Écrivains américains d'origine latino-américaine -- Entretiens.; LITERARY CRITICISM -- American -- Hispanic American.; LITERARY CRITICISM -- American -- General.; LITERARY CRITICISM -- General.; American literature -- Hispanic American authors; Children's literature, American; Hispanic American authors; Young adult literature, American; Interview; interviews.; Interviews; Interviews.